Chivalry Revisited: Gender, Race/Ethnicity, and Offense Type on Domestic Violence Charge Reduction. (April 2016) - Romain, Danielle M.; Freiburger, Tina L.
There is limited research on the role of gender in charge reduction, particularly for domestic violence cases.The purpose of this study is to test the direct and interactive effects of defendant gender, race/ethnicity, type of offense, and victim gender on charge reduction. A population census of 2, 281 domestic violence cases in a large Midwestern county was obtained from the prosecutor's office. The effect of gender varies depending on the operationalization of charge reduction. Female-on-female cases were least likely to be dismissed. Non-White females were least likely to receive a violent charge reduction. Future research on the underlying mechanisms of why female-on-female cases and non-White females are less likely to receive a reduction is needed.